2014
DOI: 10.1007/s10701-014-9860-7
|View full text |Cite
|
Sign up to set email alerts
|

A Discussion on the Properties of Gamow States

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science +Business Media New York. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
(116 reference statements)
0
10
0
Order By: Relevance
“…Correspondingly, in [49], we have shown that there are two possible expansions for the total Hamiltonian H given by the following expressions,…”
Section: A Non-hermitian Hamiltonianmentioning
confidence: 94%
See 1 more Smart Citation
“…Correspondingly, in [49], we have shown that there are two possible expansions for the total Hamiltonian H given by the following expressions,…”
Section: A Non-hermitian Hamiltonianmentioning
confidence: 94%
“…In [49], we have defined a pseudometrics for Gamow vectors. The idea of using pseudometrics was discussed heuristically in previous articles [50,51].…”
Section: B Time Evolution Operatormentioning
confidence: 99%
“…It is interesting how this formalism may be applied to Gamow states. This discussion has been already given fundamentally in [ 87 ], and here we want to discuss its main points. In order to make the arguments simpler, we shall use a two Hamiltonian model with the properties given in the previous sections, that means, its absolutely continuous spectrum of is simple, so that the absolutely continuous part of admits the following spectral decomposition [ 17 ]: with , .…”
Section: Gamow States As Functionals On An Algebra Of Operatorsmentioning
confidence: 99%
“…These coherent states satisfy a couple of resolutions of the identity in a sense to be clarified here. A spectral decomposition of the Hamiltonian in terms of the Gamow vectors has the form [32]…”
Section: Appendix 2 Resolutions Of the Identitymentioning
confidence: 99%